Regeneration of uninucleate protoplasts: a potential method for determining nuclear ratios - S. B. Galsworthy; R. L. Metzenberg (Fungal Genetics Reports, 1965)
Regeneration of uninucleate protoplasts: a potential method for determining nuclear ratios